An Activated Glassy Carbon Electrode for Rapid, Simple, and Sensitive Voltammetric Analysis of Diclofenac in Tablets - Katarzyna Tyszczuk-Rotko; Aleksy Keller; Aleksandra Liwak (Molecules)
This paper proposes an environmentally friendly sensor for determining trace amounts of diclofenac (DCF)—an activated glassy carbon electrode (aGCE). Such a sensor was achieved by simple surface activation of a glassy carbon electrode to perform five cyclic voltammetric scans from −1.5 to 2.5 V at a scan rate (υ) of 100 mV/s in 0.1 M NaOH. This type of activation results in the formation of surface functional groups, which provide several advantages such as the creation of new active sites, the improvement of electron transfer dynamics, and sensor electrocatalytic activity. The electrode prepared in this way was used to develop a new differential pulse adsorptive stripping voltammetric procedure (DPAdSV) for rapid, simple, and sensitive DCF analysis. Thanks to this procedure, the following calibration curve range was obtained: 1–100 nM with low detection and quantification limits of 0.25 and 0.83 nM, respectively. To show the practical application of the method, DCF was successfully determined in commercially available pharmaceutical preparations with the standard addition method.